A Optimalisasi Pendataan Indeks Pembangunan Manusia Dengan Teknologi Digital: Meningkatkan Efisiensi, Akurasi, dan Berkelanjutan dalam Paradigma Sirkular Ekonomi - Susilawati, Eva (The Indonesian Journal of Computer Science, 2024)
The Human Development Index (HDI) data collection is an essential process for measuring and monitoring the progress of human development in a country or region. With the shift towards increasingly integrated digital technology, the use of Android-based applications offers the potential to enhance efficiency and accuracy in the collection, analysis, and reporting of HDI data. This technology integration enables real-time and accurate data collection utilizing Geographic Information System (GIS) device sensors, thereby expanding accessibility for communities and stakeholders. The aim of this research is to improve operational effectiveness while positively impacting environmental and socio-economic sustainability. Integrating HDI data collection with a circular economy paradigm can also aid in identifying priority areas for sustainable development interventions. Based on the implementation results, practicality in the efficiency and accuracy aspects of application usage achieved 86%, categorized as "Very Practical". Therefore, these findings indicate that the developed application can enhance the optimization of HDI data collection in Cianjur Regency